Enrôler les dirigeants pour contrôler l’entreprise : le répertoire d’action des fonds d’investissement - Fabien Foureault (Revue de la Régulation)
This article deals with the relations between shareholders and managers, and between property and control of corporations within financial capitalism. One of the main drivers of financialization is the acquisition of firms by investors who try to reorient their strategies towards their interests. The case of Leveraged Buy-Outs (LBO) carried out by private equity firms shows how investors develop and implement a conception of control consisting in the indirect administration of corporations and the enrolling of managers – who should move from the role of corporate executive to the one of capitalist entrepreneur. Political control of the corporation is effective when they find a balance between distant control and close control that draw a zone of compromise between these two class fractions.